Conversion of Ostrich Eggshells (Struthio camelus) to Calcium Phosphates - (:unkn) unknown (AUSTRALIAN CERAMIC SOCIETY, 2015)
The exceptional progress made in orthopaedic and dental applications have increased the demand of calcium phosphate bioceramics due to their chemical similarities to the inorganic component of hard tissues. Low cost production of calcium phosphate bioceramics could be achieved by using pure natural biogenic materials by relatively simple methods. In this study calcium phosphate powders were produced from ostrich (Struthio camelus) eggshell powder at a moderate temperature of 80 degrees C by relatively simple process of low temperature heating by hot plate (HP) and hot platting while agitation with ultrasonication (HPUS) hence introducing mechanical activation. The product structure and compositions were studied with FTIR, SEM, DTA/TCA, XRD and ICP techniques. The results showed that calcium deficient hydroxyapatite and dicalcium phosphate were obtained from HP and HPUS methods. Poorly crystalline calcium deficient hydroxyapatite was converted into whilockite after calcining at 800 degrees C. The results suggest that this low cost and relatively simple method is efficient to easily produce calcium phosphate powders from adequately feed controlled farms to obtain pure uncontaminated eggshells for a range of biomedical applications.
Keywords: Calcium phosphates; ostrich; struthio camelus; mechanochemical; characterisation; NANOCRYSTALLINE HYDROXYAPATITE; MATRIX PROTEINS; BONE; BIOCERAMICS; SYSTEMS; PHASE